Performance modeling and analysis for many-core processors part 1(GPU) - Seet, Ivan Wei Ren. (2013)
Data analyze has become very important with growth of information today. There is a need of real-time information to be process and analyze fast. This led to the research analyze of the current many-core processor which can support fast processing of large amount of data.